Pengaruh Umur Pemotongan Terhadap Produksi Protein dan Serat Kasar Macroptilium atropurpureum - M. Nur Husin (Agricultural Faculty, 2000)
ABSTRACT.This research is intended to know the influence of cutting interval on crude protein production and crude fiber of Macroptilium atropurpureum (siratro). Treatment with cutting interval was of 5, 7, 9 and 11 weeks. Result of study showed a maximum crude protein production of siratro 563,27 kg/ha/years was fonded at the age of 9 weeks. Maximum crude fiber production of siratro 1482,53 kg/ha was founded at the age 11 weeks.